Les marchés à terme de produits pétroliers - Simon, Yves (L'Actualité économique, 1984)
ABSTRACTIn the first part of this paper a short description of the technical aspects of future markets of oil products is made. The second part is devoted to the services rendered by those markets. In the third part, the development of future markets of oil products is set forth.